MUHAMMAD NAQUIB AL ATTAS'S CONCEPT OF ISLAMIC EDUCATION IN DEVELOPING ISLAMIC BUSINESS ETHICS - Muhammad Haris Hidayatulloh; Alfiyatul Fitriyah; Muhammad Zainudin; Helmi Syaifuddin (International Journal of Economics and Management Research, 2022)
This article discusses the thoughts of the figure Muhammad Naquib al Attas who discusses the concept of thought in Islamic education and is related to its relation to Islamic business ethics. Naquib al Attas's concept related to his thoughts on Islamic education are Islamic education whose terminology is taken from the Arabic words (al-Qur'an) and al-sunnah, for example there are words tarbiyah, ta'lim, and ta'dib and some are even called riyadlah. However, according to al Attas in his study of classical books it turns out that no one uses the term tarbiyah in the meaning of education. Likewise ta'lim which is interpreted by al-Attas as teaching. So, the word ta'lim is narrower than education. On this basis, the relationship between business ethics and Islamic education has a fairly close relationship because education determines what a person's personality is like both in terms of morals and ethics. The methodology used here uses a qualitative method with a literature study approach, and is carried out by gathering supporting literature sources, both primary and secondary sources related to the discourse on the concept of Islamic education Naquib Al Attas and business ethics education.